2016
DOI: 10.1007/s00423-016-1461-9
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of mechanical bowel preparation prior to elective colorectal surgery: current insights

Abstract: Current best evidence suggests that colorectal resection should be preceded by a combination of oral antibiotics, mechanical bowel preparation and intravenous antibiotics at induction. Further randomized controlled trials are required due to a paucity of level 1 evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
0
7
0
2
Order By: Relevance
“…In contrast, some large data sets have shown that pre-operative MBP alone has no influence on post-operative complications such as SSI or AL (16,32,33). However, the combination of non-absorbable oral antibiotics with preoperative MBP was shown to be beneficial in preventing and reducing SSI and AL (18,34,35). Currently, this combination of pre-operative antibiotics and MBP is frequently used worldwide with success.…”
Section: Preoperative Mechanical Bowel Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, some large data sets have shown that pre-operative MBP alone has no influence on post-operative complications such as SSI or AL (16,32,33). However, the combination of non-absorbable oral antibiotics with preoperative MBP was shown to be beneficial in preventing and reducing SSI and AL (18,34,35). Currently, this combination of pre-operative antibiotics and MBP is frequently used worldwide with success.…”
Section: Preoperative Mechanical Bowel Preparationmentioning
confidence: 99%
“…Regrettably, controversy prevails about the impact of preoperative MBP in colorectal surgery (16)(17)(18). In their multicenter randomized trial, Si-Oen et al could not find significant difference in the outcome variables between patients with and without MBP in elective open colonic surgery (19).…”
Section: Introductionmentioning
confidence: 99%
“…For many years, bowel preparation was used less and less, as the oral antibiotic preparation was abandoned. Recently, many studies have highlighted improved outcomes with mechanical bowel preparation and oral antibiotics including decreased surgical site infection (SSI) and anastomotic leak [67][68][69][70][71]. Some data also suggests that even in the absence of a mechanical bowel preparation, oral antibiotics may still decrease the incidence of SSI following colectomy [72].…”
Section: Perioperative Prophylactic Antibiotics and Mechanical Bowel Preparationmentioning
confidence: 99%
“…Cuando se produce una solución de continuidad en el tubo digestivo, millones de microorganismos que se encuentran colonizando el colon se vierten a la cavidad abdominal, por lo que durante el acto quirúrgico debemos de cuidar la técnica para evitar, en la medida de lo posible la salida de material fecaloideo. Algunos autores aseguran que la contaminación intraoperatoria es un factor de riesgo de FA (90), (94),(109).La pérdida de sangre intraoperatoria de más de 300 ml (90) y la transfusión de sangre también son factores de riesgo independientes para la FA (110).Konishi y Ross et al observaron un menor índice de infección postoperatoria, incluida la FA, cuando se combinaba la antibioterapia intravenosa y la descontaminación digestiva con antibioterapia vía oral, que con la administración de antibióticos por vía sistémica únicamente (111),(112),(114). Sin embargo, la preparación mecánica del colon aislada no ha demostrado beneficio frente a la aparición de FA (113),(115).…”
unclassified
“…Sin embargo, la preparación mecánica del colon aislada no ha demostrado beneficio frente a la aparición de FA (113),(115). En 2016, Murray et alpublicaron que la resección colorrectal debe ir precedida de una combinación de antibióticos por vía oral, preparación mecánica del intestino y antibióticos por vía intravenosa en la inducción anestésica porque disminuye el riesgo de FA(114).La anestesia epidural produce alteraciones de la motilidad intestinal y puede favorecer la FA, aunque la mayoría de los trabajos que han incluido esta variable a estudio no ha observado un incremento significativo de la FA(116),(117),(118).La restricción de líquidos intravenosos durante una intervención quirúrgica abdominal mayor no ha demostrado un incremento de FA ni aumento del riesgo de complicaciones postoperatorias(119). A diferencia de un ensayo clínico donde se redujeron los líquidos intravenosos, y se observó hipotensión mantenida, oligoanuria o problemas con la bomba de perfusión precisándose la administración de líquidos intravenosos con la necesidad de suspender el ensayo clínico(120).Entre los factores específicos de a la técnica quirúrgica, destaca el tipo de anastomosis cólica y la localización de la tumoración y donde se secciona la vascularización del colon.Hoy en dia se piensa que la región anatómica donde se origina el foco de infección puede jugar un papel importante en la respuesta inmune.…”
unclassified